The Science of Crowds: A Genealogical Analysis of Gustave Le Bon’s Collective Psychology - Damiano Palano (Genealogy, 2025)
This article examines Gustave Le Bon’s thinking, focusing in particular on the aspects most closely connected to the search for the “laws” of the rise and fall of civilizations. Indeed, throughout his intellectual career, Le Bon cultivated the ambition of providing a credible answer to the problem of French decadence. In other words, he tried to become a kind of “Machiavelli of the age of crowds”. This article argues that this political objective affected Le Bon’s theory and his psychology of crowds. Since he wanted to make his political recipes appear credible to the elites of the Third Republic, he had to modify his theoretical architecture on nonsecondary points. He managed to hide the inconsistencies under the veil of effective rhetoric but, in retrospect, one can easily recognize that, in his theory, he uses three different ideas of the unconscious to explain the behavior of crowds, peoples, and “races”.